DETECTION OF CELLULAR-IMMUNITY WITH THE SOLUBLE-ANTIGEN OF THE FUNGUS SPOROTHRIX-SCHENCKII IN THE SYSTEMIC FORM OF THE DISEASE - Carlos, I. Z.; Sgarbi, DBD; Angluster, J.; Alviano, C. S.; Silva, C. L. (Kluwer Academic Publ, 1992)
Sporothrix schenckii is the etiologic agent of sporotrichosis, a mycosis of world-wide distribution more commonly occurring in tropical regions. The immunological mechanisms involved in the prevention and control of sporotrichosis are not fully understood but apparently include both the humoral and cellular responses. In the present investigation, cellular immunity was evaluated by in vivo and in vitro tests in mice infected with yeast-like forms of S. schenckii. The disease developed systemically and cellular immunity was evaluated for a period of 10 weeks. The soluble antigen utilized in the tests was prepared from yeast form of the fungus through the sonication (20 min: 10 sonications at 50 W at 2-min intervals). Delayed hypersensitivity and lymphocyte transformation tests showed that the cellular immune response was depressed between the 4th and 6th week of infection when the animals were challenged with the soluble fungal antigen. This depression frequently indicates worsening of the disease, with greater involvement of the host. This is a promising field of research for a better understanding of the pathogeny of this mycosis.
Keywords: CELLULAR IMMUNITY; SPOROTRICHOSIS; SPOROTHRIX-SCHENCKII